2015
DOI: 10.1007/s11481-015-9636-7
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Seeking and Drug Addiction in Humans and Animals: From Behavior to Molecules

Abstract: Global treatment of drug addiction costs society billions of dollars annually, but current psychopharmacological therapies have not been successful at desired rates. The increasing number of individuals suffering from substance abuse has turned attention to what makes some people more vulnerable to drug addiction than others. One personality trait that stands out as a contributing factor is novelty seeking. Novelty seeking, affected by both genetic and environmental factors, is defined as the tendency to desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 121 publications
(225 reference statements)
9
88
0
Order By: Relevance
“…Minor allele frequencies are typically higher in mouse populations than human populations, rendering possible the detection of small effect alleles. Selective breeding for behavioral phenotypes that correlate with drug‐seeking behaviors enriches and genetically fixes risk alleles . In a study with high responder and low responder rats selectively bred based on exploratory locomotion in a novel environment, seven genome‐wide significant loci accounted for approximately one‐third of total variance and two‐thirds of genetic variance selected for this trait .…”
Section: Genetics and Genomic Tools Can Show The Nature Of Sex Differmentioning
confidence: 99%
“…Minor allele frequencies are typically higher in mouse populations than human populations, rendering possible the detection of small effect alleles. Selective breeding for behavioral phenotypes that correlate with drug‐seeking behaviors enriches and genetically fixes risk alleles . In a study with high responder and low responder rats selectively bred based on exploratory locomotion in a novel environment, seven genome‐wide significant loci accounted for approximately one‐third of total variance and two‐thirds of genetic variance selected for this trait .…”
Section: Genetics and Genomic Tools Can Show The Nature Of Sex Differmentioning
confidence: 99%
“…Although it is as yet unclear whether oxytocin and dopamine have a direct association, accumulating evidence has suggested that oxytocin may have a positive effect on treatment for alcohol use disorders and other problematic substance abuse [16, 17]. In addition, there could exist an association between dopamine and novelty-seeking tendency [18], which could be an important issue related to addiction and oxytocin [19-21]. …”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, we found an association between COMT rs4680 and NS in the whole sample, partially consistent with literature data that links dopaminergic transmission with this TCI dimension. In particular, it has been hypothesized that NS is modulated by the dopaminergic activity within the midbrain dopaminergic neurons (e.g., [60, 61], which in turn is regulated by the meso-cortical dopaminergic pathway (e.g., [27, 62, 63]). Thus, it could be hypothesized that the low-dopaminergic activity associated with the Val/Val genotype within the meso-cortical dopaminergic pathway leads to an upregulation of the mesolimbic pathway, which in turn determines higher NS levels.…”
Section: Discussionmentioning
confidence: 99%